CCIE routing and switching practice labs - Duggan, Martin (CCIE self-study., 2004)
Six comprehensive CCIE routing and switching labs to hone configuration and troubleshooting skills Prepare for the CCIE lab exams and hone your configuration and troubleshooting skills with six complete practice scenarios that cover: Frame Relay configuration 3550 switch configuration ATM PVC and SVC configuration IP routing protocol configuration, including RIPv2, EIGRP, OSPF, and IS-IS Route redistribution IBGP and EBGP configuration IP multicast Security IP and IOS features DLSw over Ethernet Voice over IP The CCIE program is designed to help individuals, companies, industries, and countries succeed in the networked world by distinguishing the top echelon of internetworking experts. CCIE candidates must not only demonstrate knowledge of a broad range of subject matter at an advanced level but also prove their ability to analyze complex problems and pose solutions in time critical settings. CCIE Routing and Switching Practice Labs provides a series of complete practice labs that mirror the difficult CCIE hands-on lab exam. Written by a CCIE program manager and a CCIE engineer, this book lays out six unique end-to-end scenarios that are both complex and realistic, providing you with the practice needed to prepare for your lab examination and develop critical-thinking skills that are essential for resolving complex, real-world routing and switching problems. CCIE Routing and Switching Practice Labs does not waste time covering conceptual knowledge found in other manuals but focuses exclusively on six complex scenarios. The structure of each chapter is the same, covering a broad range of topics. Each chapter starts with a set of pre-lab tasks and general guidelines that outline instructions for each exercise. This is followed by the timed practice exam questions. Each chapter then wraps up with an Ask the Proctor section that provides hints and clues to the solutions and a Lab Debrief, which analyzes the answer to each question. The companion CD-ROM contains solutions for all of the labs, including configurations and common show command output from all the devices in the topology. "This book possesses solid and practical guidance for anyone pounding away at the keyboard whether it is for the pursuit of the CCIE or the pursuit of the source of a real problem."--Kathe Saccenti, CCIE Product Manager, Cisco Systems, Incorporated CCIE Routing and Switching Practice Labs is part of a customized learning path from Cisco Systems that includes simulation and ha ...